Effect of β − hydroxy − γ -aminophosphonate (β − HPC) on the hydrolytic activity of Nocardia brasiliensis as determined by FT−IR spectrometry - Martínez-Robles, Sandra; González-Ballesteros, Erik; Reyes-Esparza, Jorge; Trejo-Teniente, Isaí; Jaramillo-Loranca, Blanca Estela; Téllez-Jurado, Alejandro; Vázquez-Valadez, Víctor H.; Angeles, Enrique; Vargas Hernández, Genaro (Frontiers in Microbiology, 2023)
Mycetoma is a chronic granulomatous disease caused by multiple species of bacteria (actinomycetoma) and fungi (eumycetoma). It affects skin, subcutaneous tissue, fascia, and bone, was recently included in the list of "Neglected Tropical Diseases'' of the World Health Organization. It is endemic in several regions of Africa, Asia, and America. In Mexico, the main causal agent is the bacterium Nocardia brasiliensis. Successful medical treatment of mycetoma is difficult because its prolonged duration is associated with adverse pharmacological effects and with the abandonment of treatment without having eliminated the infection. The use of immune and metabolic modulating agents has been considered a better strategy to improve the effectiveness of conventional antimicrobial treatments. Based on the relevance of L-carnitine, mainly in fatty acid metabolism and energy production by β-oxidation, a more soluble and stable analogue β-hydroxy-γ-aminophosphonate (β-HPC), was, synthesized, and studied in different pathologies, among which was an experimental murine model of actinomycetoma. Because of the beneficial therapeutic effect observed in the model of actinomycetoma and the known role of L-carnitine and related compounds in bacterial physiology and metabolism, we set out to investigate the direct effect of β-HPC on the metabolism of N. brasiliensis. To analyze the effect of β-HPC on themetabolic capacity for the hydrolysis of the substrate’s casein, L-tyrosine, egg yolk, and tween 80, Fourier-Transform Infrared Spectroscopy (FT-IR) was employed. It was found that β-HPC increase the metabolic activity of N. brasiliensis associated with the improved growth and increased hydrolysis of the substrates analyzed. It was observed that, in the case of L-tyrosine hydrolysis, the aromatic ring and the functional groups were degraded. At 1515 cm-1, any signal or peak distinctive of this amino acid was absent but was present at 839, 720, 647, and 550 cm-1. The use of FT-IR spectroscopy technology allowed us to demonstrate enhanced hydrolysis and the spectrum of N. brasiliensis with a large OH peak in the fingerprint. Moreover, is a fast, easy-to-use, and economical option for the biochemical characterization of N. brasiliensis that, together with conventional diagnostic techniques, facilitates the identification of this bacterium as a causal agent in cases of actinomycetoma.